Fiona Terry of the International Committee of the Red Cross talks about The Roots of Restraint in War and the intersection of research and humanitarianism. Issue 1 (April 2020) - Terry, Fiona; Kinsella, Helen M.; Straus, Scott
Fiona Terry is the Head of the Centre for Operational Research and Experience at the International Committee of the Red Cross (ICRC). She is the co-author of The Roots of Restraint in War (https://www.icrc.org/en/publication/4352-roots-restraint-war ), which the ICRC published in 2018. The report examines how and why formal and informal norms shape armed group behavior in war. In addition to discussing some of the report's main findings, the interview addresses the relationship between academic research and humanitarian practitioners; how external researchers are able, or not able, to shape internal organizational culture; the ethics of data collection; gender and the laws of war; and the differences between formal state militaries and other kinds of non-state actors that engage in violence. The interview was conducted by Helen M. Kinsella, Associate Professor of Political Science at the University of Minnesota, and Scott Straus, co-editor-in-chief of the journal. Author of The Image before the Weapon: A Critical History of the Distinction between Combatant and Civilian, Kinsella was a Council on Foreign Relations Fellow at the ICRC, where she focused on gender and armed conflict, in the 2018–2019 academic year.